CD9 and CD81 Interactions and Their Structural Modelling in Sperm Prior to Fertilization - Frolikova, Michaela; Manaskova-Postlerova, Pavla; Cerny, Jiri; Jankovicova, Jana; Simonik, Ondrej; Pohlova, Alzbeta; Secova, Petra; Antalikova, Jana; Dvorakova-Hortova, Katerina (International journal of molecular sciences, 2018)
Proteins CD9 and CD81 are members of the tetraspanin superfamily and were detected in mammalian sperm, where they are suspected to form an active tetraspanin web and to participate in sperm⁻egg membrane fusion. The importance of these two proteins during the early stages of fertilization is supported by the complete sterility of CD9/CD81 double null female mice. In this study, the putative mechanism of CD9/CD81 involvement in tetraspanin web formation in sperm and its activity prior to fertilization was addressed. Confocal microscopy and colocalization assay was used to determine a mutual CD9/CD81 localization visualised in detail by super-resolution microscopy, and their interaction was address by co-immunoprecipitation. The species-specific traits in CD9 and CD81 distribution during sperm maturation were compared between mice and humans. A mutual position of CD9/CD81 is shown in human spermatozoa in the acrosomal cap, however in mice, CD9 and CD81 occupy a distinct area. During the acrosome reaction in human sperm, only CD9 is relocated, compared to the relocation of both proteins in mice. The structural modelling of CD9 and CD81 homologous and possibly heterologous network formation was used to propose their lateral Cis as well as Trans interactions within the sperm membrane and during sperm⁻egg membrane fusion.
Keywords: antigeny CD9; Male; Tetraspanin 29; Sperm Capacitation; tetraspanin network; akrozomální reakce; fertilization; Fertilization; acrosome reaction; Protein Interaction Maps; mouse; structural modelling; Spermatozoa; mužské pohlaví; Tetraspanin 28; Acrosome Reaction; capacitation; sperm; fúze membrán; molekulární modely; human; Membrane Fusion; Models, Molecular; Animals; lidé; kapacitace spermií; antigeny CD81; ženské pohlaví; Humans; zvířata; CD9; myši inbrední C57BL; spermie; myši; Mice, Inbred C57BL; CD81; membrane fusion; mapy interakcí proteinů; Mice; Female; fertilizace